PENGEMBANGAN BAHAN AJAR BERBASIS ANDROID MENGGUNAKAN SMART APPS CREATOR PADA TEKS EKSPLANASI KELAS XI SMK SWASTA PAB 2 HELVETIA - Kurniati, Dwi; Rita, Rita; Safina, Nila (Jurnal Bahastra, 2023)
This study aimed to describe the process of development, validation, feasibility, and effectiveness of using Android-based teaching materials with smart apps creators in explanatory texts for class XI SMK. This study was conducted in SMKS PAB 2 Helvetia. The research method is Research and Development (RD) with ADDIE model including: Analysis, Design, Development, Implementation, Evaluation with a population as 238 students. This study used a purposive sampling technique with a total of 36 students. The types of data in this study include qualitative and quantitative data. The result of this study is an android-based teaching material product. According to the results of validation from material experts I can be categorized as "Satisfactory" and feasible to be tested (77%). The results of material expert validation II can be categorized as "Very Satisfactory" and feasible to be tested (85%). Meanwhile, the results of media experts I can be categorized as "Very Satisfactory" and feasible to be tested (90%). The results of media experts II can be categorized as "Very Satisfactory" and feasible to be tested (91%). According to the results of the teacher's response, 94% was categorized as "Very Satisfactory" with decent qualifications. While the results of student responses from 36 students get a percentage that has been converted with the qualification "Very Satisfactory" as 92% and it was said to be effectively used. Then it can be concluded that the android-based teaching materials developed are effective and suitable to be used in learning in the classroom.